Management of Recurrent Endometrial Cancer or Atypical Endometrial Hyperplasia Patients After Primary Fertility-Sparing Therapy - Chen, Junyu; Cao, Dongyan; Yang, Jiaxin; Yu, Mei; Zhou, Huimei; Cheng, Ninghai; Wang, Jinhui; Zhang, Ying; Peng, Peng; Shen, Keng (Frontiers in Oncology, 2021)
Objective To evaluate the efficacy and prognosis of fertility-sparing re-treatment on patients with recurrent endometrial cancer (EC) and atypical endometrial hyperplasia (AEH) who wish to preserve their uterus after complete remission (CR) for primary conservative therapy. Methods We performed a retrospective study on recurrent EC or AEH patients who received fertility-sparing re-treatment after achieving CR. Data regarding clinicopathological factors, adverse events, treatment efficacy, tumor prognosis, and reproductive outcome were analyzed. Results Of the 98 recurrent patients with a median disease-free interval period of 19 (3–96) months, 18 patients decided to receive hysterectomy directly, and 80 patients received fertility-preserving re-treatment. Seventy-one (88.6%) cases achieved CR, 96.0% in AEH and 75.8% in EC patients, with the 6 (3–16) months’ median CR time. Seven (8.8%) patients failed to achieve CR and then underwent the hysterectomy: one partial response (PR), four stable disease (SD), and two progressive disease (PD). Forty-nine women attempted to get pregnant after CR, 13 (26.5%) became pregnant, seven (14.3%) successfully delivered, and six (12.2%) miscarried. During the follow-up period, 22 (31.0%) women had developed a second relapse with the median recurrence time of 12 (4–90) months, and 10 patients decided to receive the third round of fertility-sparing treatment. Seven (70.0%) patients, 33.3% in EC and 85.7% in AEH, achieved CR again. Hysterectomy was performed in two (20.0%) patients due to SD. After the third-round treatment, six women had the desire to conceive but no one became pregnant successfully. Conclusion For patients with recurrent EC and AEH after primary conservative treatment, fertility-preserving re-treatment can still achieve a promising response, and patients have possibilities of completing childbirth.